Neuropeptide F immunoreactive clock neurons modify evening locomotor activity and free-running period in Drosophila melanogaster. - Hermann, C.; Yoshii, T.; Dusik, V.; Helfrich-Förster, C. (Journal of Comparative Neurology, 2012)
Different subsets of Drosophila melanogaster's clock neurons are characterized by their specific functions in daily locomotor rhythms and the differences in their neurotransmitter composition. We investigated the function of the neuropeptide F (NPF) immunoreactive clock neurons in the rhythmic locomotor behavior of adult flies. We newly identified the fifth s-LN(v) and a subset of the l-LN(v)s as NPF-positive in addition to the three LN(d)s that have been described previously. We then selectively ablated different subsets of NPF-expressing neurons using npfGal4-targeted expression of the cell death gene head involution defective (hid) in combination with cryGal80 and pdfGal80. By analyzing daily locomotor rhythms in these flies, we show that the NPF-positive clock neurons--especially the fifth s-LN(v) and the LN(d)s--are involved in both the control of the free-running period in constant darkness (DD) and the phasing and amplitude of the evening activity in light-dark (LD) cycles. Furthermore, we show that the simultaneous ablation of NPF and pigment dispersing factor (PDF)-immunoreactive neurons has additive effects in LD, resulting in an evening peak phase that is even more advanced in comparison to PDF-ablated flies. We also found that this more advanced evening peak is additionally reduced in amplitude. To putatively assign the observed phenotypes to the action of NPF, we knocked it down in conjunction with PDF using RNA-interference (RNAi) and further suggest a possible role for NPF in the control of the flies' evening activity.